1999
DOI: 10.1021/jp982715i
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Solvent-Exposed Salt-Bridges

Abstract: This paper uses a recently developed computer model to study the energetics of solvent-exposed salt-bridges. The model uses the "mining minima" method to compute conformational free energies with the CHARMm empirical force and the generalized Born solvation model. Satisfactory agreement is obtained in comparison with the measured binding affinities of ion pairs in solution and with the salt-bridge energetics deduced from studies of salt-bridges in helical peptides. The calculations suggest that stabilizing cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 63 publications
3
56
0
Order By: Relevance
“…Our applications of a GB model 3 in which atomic selfenergies are estimated with a charge-induced dipole term, 36 have yielded good agreement with experiment for pK a shifts in small molecules, 37 ion-pairing in aqueous solution, 38 the binding affinities of small molecules in chloroform, 39 conformational analysis of a potent HIV protease inhibitor, 40 and the association of adenine with synthetic adenine receptors (article in preparation). On the other hand, the GB model was not particularly effective at selecting the correct bound conformation of protein-ligand complexes, 41 and it gave somewhat unsatisfying results in calculations of the pK a s of ionizable groups in a protein active site.…”
mentioning
confidence: 70%
“…Our applications of a GB model 3 in which atomic selfenergies are estimated with a charge-induced dipole term, 36 have yielded good agreement with experiment for pK a shifts in small molecules, 37 ion-pairing in aqueous solution, 38 the binding affinities of small molecules in chloroform, 39 conformational analysis of a potent HIV protease inhibitor, 40 and the association of adenine with synthetic adenine receptors (article in preparation). On the other hand, the GB model was not particularly effective at selecting the correct bound conformation of protein-ligand complexes, 41 and it gave somewhat unsatisfying results in calculations of the pK a s of ionizable groups in a protein active site.…”
mentioning
confidence: 70%
“…According to a systematic geometric analysis of the Brookhaven Protein Data Bank, the stereochemistry of the side-chain H-bonds of proteins was pointed out to be characterized by at least three factors: (a) the electronic configuration of the H-bond acceptor atoms, (b) the steric accessibility of the H-bond donor atoms, and (c) the conformation of amino acid side-chains. 27 There have also been a number of theoretical studies aimed at quantifying the strength of interaction of small ions, 9,15,26,[28][29][30][31][32][33][34][35][36][37] mimicking the salt bridges between the CO − 2 side group of glutamate or asparate and the guanidinium side group of the arginine. In particular, the interaction energy in the Arg-Glu salt bridge varies from 35 [45][46][47][48][49] The IR spectrum was evaluated in some papers; 45,49 however, the 2000-2800 frequency region was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…1). It was suggested that Arg379 and Lys386 of p53 could form salt bridges with Glu45 and Glu86 of S100B(ββ), respectively 32 ; however, exposed salt-bridges are rarely stabilizing 33 . In fact, p53 Lys386 and S100B(ββ) Glu86 are spatially close enough to make saltbridge contact only ~15% of the time in the NMR ensemble (see Fig.…”
Section: Introductionmentioning
confidence: 99%